Influencia de la dextranasa L-650X en el jugo de la caña de azúcar para minimizar la presencia de la dextrana - Verde Montoya, Esmeralda Lili (2014)
This project aims to apply an enzyme called L-650X Dextranase which helps to minimize dextran in cane juice without altering the actual operating conditions of the Company. The cane juice of first mill will be used as working material and analysis. There will be used as operating variables: temperature, pH, enzyme concentration and time. For the development of these analyzes are used: pH meter, refractometer, and spectrophotometer